Modification of Gold Surface with Gold Nanoparticles and Cyclohexyl Dithiocarbamate as a Selective Sensor for Cysteine - Ehab AlShamaileh; Haytham Saadeh; Valerie Favry (Journal of Chemistry)
The self-assembly of cyclohexylamine dithiocarbamate (C6DTC) on gold (Au) and gold nanoparticles (AuNPs) was studied electrochemically using cyclic voltammetry (CV). Cyclic voltammetry was used to study the system Fe(CN)63-/Fe(CN)64- at the electrode surface of (C6DTC/Au) and (C6DTC/AuNPs). The application of the resulting chemically modified surface as a selective sensor for cysteine, among other amino acids, was investigated. Linear oxidative desorption technique was used to characterize the modified electrode that consists of the self-assembled monolayer of cyclohexylamine dithiocarbamate on gold nanoparticles deposited on Au electrode (C6DTC/AuNPs/Au). The results showed an enhancement in the oxidation peak of cysteine on the modified electrode and hence a greater sensitivity.